Bring a map when exploring the ERP data processing multiverse: A commentary on Clayson et al. 2021 - Daniel Feuerriegel; Stefan Bode (NeuroImage, 2022)
Clayson et al. (2021) describe an innovative multiverse analysis to evaluate effects of data processing choices on event-related potential (ERP) measures. Based on their results, they provide data processing recommendations for studies measuring the error-related negativity and error positivity components. We argue that, although their data-driven approach is useful for identifying how data processing choices influence ERP results, it is not sufficient for devising optimal data processing pipelines. As an example, we focus on the inappropriate use of pre-response ERP baselines in their analyses, which leads to biased error positivity amplitude measures. Results of multiverse analyses should be supplemented with further investigation into why differences in ERP results occur across data processing choices before devising general recommendations.